2007
DOI: 10.1002/ajh.21062
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transplant hepatosplenic T‐cell lymphoma successfully treated with hyperCVAD regimen

Abstract: Hepatosplenic T‐cell lymphoma (HSTL) is an aggressive lymphoma. In post‐transplant immunosuppressed patients, HSTL is usually rapidly fatal. We report successful treatment of post‐transplant HSTL in a 50‐year‐old renal allograft recipient by reducing immunosuppression and using intensive chemotherapy consisting of alternating cycles of HyperCVAD (cyclophosphamide, vincristine, doxorubicin, and dexamethasone) and MTX/HiDAC (methotrexate, Ara‐C). Remission is ongoing at 8+ years. Literature review identified ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Patients are often young males who present with a systemic illness with fever, enlarged liver and spleen, and cytopenias. This lymphoma has been reported in patients with an altered immune system, including Crohn's disease [44] and after renal transplantation [45,46]. In the absence of a high degree of suspicion, the diagnosis might be overlooked.…”
Section: Hepatosplenic T-cell Lymphomamentioning
confidence: 99%
“…Patients are often young males who present with a systemic illness with fever, enlarged liver and spleen, and cytopenias. This lymphoma has been reported in patients with an altered immune system, including Crohn's disease [44] and after renal transplantation [45,46]. In the absence of a high degree of suspicion, the diagnosis might be overlooked.…”
Section: Hepatosplenic T-cell Lymphomamentioning
confidence: 99%
“…To date, 36 cases of HSTCL have been reported in IBD patients (Kotlyar et al, 2011), mostly affecting young men and the prognosis has been invariably fatal. Despite treatment with chemotherapy and stem cell transplantation, median survival is only 11 months (Falchook et al, 2009) but novel treatment strategies have shown some promise in isolated cases (Jaeger et al, 2008, Tey et al, 2008. Diagnosis is made by liver, splenic or bone marrow biopsy exhibiting atypical medium-sized lymphoid cells with round nuclei, small distinct nucleoli, loosely condensed chromatin, moderate pale cytoplasm and particular immunophenotypic expression which will be discussed further (Swerdlow et al, 2008).…”
Section: Hepatosplenic T-cell Lymphomamentioning
confidence: 99%
“…It is interesting that, HSTCL has only been reported in a single non-IBD patient who received adalimumab for rheumatoid arthritis (Shale et al, 2008). Conversely, there are a number of case reports of patients developing HSTCL whilst on immunosuppression in the post-transplant setting (Roelandt et al, 2009, Tey et al, 2008, Steurer et al, 2002 where anti-TNF drugs are not used.…”
Section: Hstcl In Ibdmentioning
confidence: 99%
“…Large prospective series did indicate a higher relapse rate and a poorer survival for PTCL than DLBCL [2,[5][6][7][8][9][10][11][12][13]. Various chemotherapy regimens have been tried out--such as MegaCHOP (intensive or higher dose of CHOP) with or without etoposide [14,15], epirubicin substituted for doxorubicin and addition of bleomycin (CEOP-B) [16], CMED (cyclophosphamide, etoposide, methotrexate, and dexamethasone) [17], CHOP or MegaCHOP/ESHAP (etoposide, cisplatin, cytarabine and prednisone) [18,19] and VCAP-AMP-VECP (vincristine, cyclophosphamide, doxorubicin, and prednisone (VCAP); doxorubicin, ranimustine, and prednisone (AMP); vindesine, etoposide, carboplatin, and prednisone (VECP)) [20]; fractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone alternating with high doses of methotrexate and cytarabine (hyperCVAD) [21,22]--with no superior efficacy to CHOP except CMED at the expense of higher treatment toxicity. Gemcitabine-based chemotherapies are emerging and seem quite compromising [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Fractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone (hyperCVAD) alternating with high doses of methotrexate and cytarabine has been used in treating PTCL [21] but did not show favorable outcome than CHOP [22]. However, alemtuzumab in combination with hyperCVAD has not been evaluated before.…”
Section: Introductionmentioning
confidence: 99%